2022
DOI: 10.3390/geosciences12040143
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Tracers of Cretaceous Arctic Paleoprecipitation

Abstract: We report estimated stable isotope compositions of depositional waters and paleoprecipitation from the Cretaceous Arctic to further elucidate the role of the global hydrologic cycle in sustaining polar warmth during that period. Estimates are based on new hydrogen isotopic analyses of n-alkane biomarkers extracted from Late Cretaceous and mid-Cretaceous terrestrial deposits in northern Alaska and the Canadian High Arctic. We integrate these new results with earlier published work on oxygen isotopic analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 85 publications
4
7
0
Order By: Relevance
“…This could be the result of geographic, orographic, or geochronological differences between the paleosol and bentonite localities. Regardless, these oxygen isotope estimates of meteoric water fall within previously reported data from paleosol siderites, dinosaur tooth enamel phosphate, and pedogenic clay minerals [4,5], and both the bentonite and paleosol localities record deuterium excess despite the large shift in oxygen isotopic composition of meteoric water.…”
Section: Implications Of δ 18 O and δD Of Meteoric Water From Pedogen...supporting
confidence: 87%
See 4 more Smart Citations
“…This could be the result of geographic, orographic, or geochronological differences between the paleosol and bentonite localities. Regardless, these oxygen isotope estimates of meteoric water fall within previously reported data from paleosol siderites, dinosaur tooth enamel phosphate, and pedogenic clay minerals [4,5], and both the bentonite and paleosol localities record deuterium excess despite the large shift in oxygen isotopic composition of meteoric water.…”
Section: Implications Of δ 18 O and δD Of Meteoric Water From Pedogen...supporting
confidence: 87%
“…Clay mineral analyses by Salazar-Jaramillo et al [14] showed no ordering of illite during I/S interstratification analyses of paleosols in the Prince Creek Formation, suggesting little or no diagenetic transformations of illite [46]. Furthermore, the results presented in Figure 5 indicate reasonable oxygen and hydrogen isotopic values of estimated meteoric water that are within the range of previously published isotopic estimates of meteoric water from the Prince Creek Formation using alternative proxies, including pedogenic siderite, dinosaurian tooth enamel phosphates, and n-alkane biomarkers [5].…”
supporting
confidence: 76%
See 3 more Smart Citations